Doppelganger - Hautman, Pete, 1952- (Hautman, Pete, 1952- Bloodwater., 2008)
High school newspaper reporter Roni Delicata finds an age-progressed photo of a missing child that looks just like her sidekick, Brian, throwing the pair into an investigation of Brian's past and family heritage.